Implementasi Kaidah al-Yaqinu La Yuzalu Bi al-Syak Dalam Fiqh Munakahat - Ah. Soni Irawan; Nina Agus Hariati (FIQHUL HADITS : Jurnal Kajian Hadits dan Hukum Islam, 2024)
The application of fiqh rules is not only focused on individual problems and worship (individual-vertical), but it’s also applied as a solution to various problems related to social-horizontal, one of which is a rule that explains the concept of convenience in order to eliminate burdens, difficulties and obstacles due to doubts in establishing a law correctly and with certainty, so that the right way is needed to determine the existence of legal certainty, that is by eliminating all doubts in it. This research aims to describe the implementation of the rules of al-yaqinu la yuzalu bi al-syak fiqh in relation to Islamic marriage law issues. This type of research is library research with a normative juridical approach. The results of the research show that this rule can be applied in several fiqh munakahat issues such as if there is doubt about the validity of the marriage due to a dispute between the two witnesses, doubt about the pronunciation of the husband's talaq kinayah towards his wife, doubt in determining when the woman's 'iddah period ends after her husband divorces her and various other munakahat fiqh issues.